2008
DOI: 10.1086/589971
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-Rays Associated with Type III Radio Bursts

Abstract: During a period of 12 minutes on 2002 July 19 14:23-14:35 UT, the WAVES instrument on WIND observed six interplanetary type III radio bursts, one approximately every 2 minutes, and each was accompanied by a weak hard X-ray (HXR) burst (12-15 keV) observed by RHESSI. The radio bursts are observed up to 150 MHz with some up to 600 MHz. Simultaneous observations by TRACE show jetlike eruptions emanating from the region of HXR emission. The observed HXRs are inconsistent with emission from the escaping type III-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
(30 reference statements)
3
18
1
Order By: Relevance
“…6), which is suggestive of the important role of magnetic reconnection in generating both phenomena. Christe et al (2008).…”
Section: Rhessi Observationsmentioning
confidence: 99%
“…6), which is suggestive of the important role of magnetic reconnection in generating both phenomena. Christe et al (2008).…”
Section: Rhessi Observationsmentioning
confidence: 99%
“…The very low energies of impulsive event electrons (typically ∼1 keV but sometimes reaching ∼0.1 keV) suggests that the acceleration may be occurring high in the corona (Lin et al 1995), thus these events are often referred to as "coronal flares" (Lin 1985). RHESSI (with attenuators out) has detected very weak 3-15 keV X-ray bursts in coincidence with type-III radio bursts (Christe et al 2008), suggesting a coronal explosion. Associations with jets observed in EUV that occur close to a coronal hole boundary (Wang et al 2006), and with fast (≥600 km s −1 ) narrow (≤20 • ) CMEs (Kahler et al 2001;Haggerty and Roelof 2002;Wang et al 2011) have also been reported.…”
Section: Flares and Impulsive Sepsmentioning
confidence: 99%
“…Observations show that in active regions during flares the temperature T h is greater than ∼10 MK and can reach up to ∼50 MK [ Lin , 1974; Benz , 1993; Aschwanden et al , 1995; Feldman et al , 1996; Christe et al , 2008]. We investigate here the effects of varying T h on remote type III emission.…”
Section: Effects Of Varying Electron Heating Parametersmentioning
confidence: 99%